2020
DOI: 10.20944/preprints202003.0042.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Screening of Inhibitors Against Spike Glycoprotein of SARS-CoV-2: A Drug Repurposing Approach

Abstract: The novel coronavirus (SARS-CoV-2) is a human pathogen recently emerged in China, causing a global pandemic of severe respiratory illness (COVID19). SARS-CoV-2 makes entry into human cells through its spike (S) protein that binds to cell surface receptors. Widespread of SARS-CoV-2 has been attributed to high affinity of S protein to its receptor. A homology model of the receptor binding domain of SARS-CoV-2 S protein (RBD) was built. RBD- receptor docking and published molecular dynamics data were used to map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Working with two different possible RBD binding sites represents an advantage as compared to other similar studies, where a single but larger binding site on the RBD was defined. 18 , 69 Indeed, as previously said, most of the currently available drugs are small molecules which are able to interact with a limited surface and only with a few residues. Therefore, selecting two binding sites corresponding to specific hot spot clusters makes the docking pose search more efficient, by limiting the search space.…”
Section: Resultsmentioning
confidence: 99%
“…Working with two different possible RBD binding sites represents an advantage as compared to other similar studies, where a single but larger binding site on the RBD was defined. 18 , 69 Indeed, as previously said, most of the currently available drugs are small molecules which are able to interact with a limited surface and only with a few residues. Therefore, selecting two binding sites corresponding to specific hot spot clusters makes the docking pose search more efficient, by limiting the search space.…”
Section: Resultsmentioning
confidence: 99%
“…In a molecular docking study, zafirlukast was identified to interact significantly with 3CL pro49 . According to other virtual screenings conducted from homology models of receptor binding domain, zafirlukast may have the potential to inhibit the binding of another SARS-CoV-2 protein, the spike glycoprotein, to the ACE-2 receptor, adding another potential mechanism of action of the drug against viral infection 50,51 . Another deep learning study using MACCS fingerprints as molecular representations predicted this drug to inhibit 3CL pro52 .…”
Section: Discussionmentioning
confidence: 99%
“…The assay stands on a simple colorimetric ELISA platform, which measures the binding between immobilized SARS-CoV-2 S protein RBD (receptor binding domain) and Human ACE2 protein [51]. The tests can be used in the screening of inhibitors in SARS-CoV-2 binding tests or drug development against spike glycoprotein of SARS-CoV-2 [52], and a potential to develop a screening kit for the SARS-CoV-2 main protein (M protein) exists [53].…”
Section: Point-of-care Tests: Poctmentioning
confidence: 99%